تفہیم القرآن میں تفسیری آراء کی اصلاح پر مبنی تنقیدات: The Rectifying Critique on Notes in Tafheem Ul Quran - Zujajah,; Prof Dr Muddassir Ahmad, (Al Manhal Research Journal, 2025)
The reviewing criticism of some explanatory notes in Tafheemul Quran was reported by the top leading Islamic scholars. Syed Abul Ala Maudoodi accepted them with thanks because he himself had been invited to correct and rectify before final publication. Most of the changes were endorsed on the issues of translations of the Qur'anic verses. A few words were skipped, which were added on the indications. Relating verses are about fasting, pilgrimage, fixed-time marriage, and perversions. The status of the mother of Ummah Hazrat Javairia was classified. The reviewing critique was conveyed by renowned personality Mahir ul Qadri the famous Maulana Muhammad Ishaque Bhatti, and Dr. Hameedullah from Paris contributed a lot. The most proper and suitable coinciding rectification was delivered by Maulana Muhammad Chiragh. He wrote and posted thirty-eight letters to Syed Abul Ala Maudoodi, which were responded to with forty-one corrections in Tafheemul Quran. All the reviewing criticisms were positive to be endorsed.